Conocimientos y prácticas sobre prevención y manejo de enfermedad diarreica aguda, en madres de niños/as del Centro Infantil del Buen Vivir Infancia Universitaria sección matutina MIES, Loja 2014-2015 - Chico Cumbicos, Bolivar Fernado (2015)
The acute diarrhea constitute a public health problem in the majority of developing countries and is the main cause of morbidity and mortality during childhood, its relation with undernourishment and the high cost of the health system and the high demand of ambulatory and hospitable attention. The present investigation pretended to determine the knowledge and maternal practice about prevention and management of acute diarrheal disease. The study was of a descriptive type, in which was applied a survey to fifty mothers of children who assist to CIBIV, the informatics program used for processing and representing information in tables was Excel. The results indicate that, the majority of mothers do not know about the risk factors to develop this pathology and the measures that decrease the danger of producing it; a great number of the respondents do not know the management of the acute diarrheal disease, the symptoms, the urgent to take the child to a health facility, and also the signs of dehydration. Regarding the practice about prevention of acute diarrheal disease, mothers give complementary feeding to children from 6 months and above, manage the disposal of waste water and the exclusive breast feeding. In respect of the management practice of acute diarrheal disease, mothers give the child homemade rehydration serum immediately and on free demand, continuing with breastfeeding and the daily diet. KEY WORDS Acute diarrheal disease, Knowledge, Practice, Prevention.